Prediksi Voltage Stability Index (VSI) Metode Artificial Neural Network (ANN) untuk Mendeteksi Tegangan Jatuh - Dimas Fajar Uman Putra; Aji Akbar Firdaus; Novian Uman Putra; Ontoseno Penangsang (Rektorat Universitas Putra Indonesia YPTK Padang, 2022)
Voltage stability analysis is needed in the planning or operation of electric power systems. This will have an impact on decreasing the system voltage and result in a voltage collapse and will be fatal resulting in a partial or total system blackout. If there is a change in load on a line, it can cause a decrease in the voltage profile. Predicting the value of additional load on a bus based on a voltage stability analysis can be done to detect the occurrence of a voltage drop. There are various methods for analyzing voltage stability, one of which is the point of voltage instability which can be determined using the Fast Voltage Stability Index (FVSI) method. Artificial Neural Network (ANN) is chosen in this problem to predict the value of the additional load.